Akses Pelayanan Kesehatan terhadap Perilaku Merokok - Ratih Indraswari (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Smoking caused 235.000 Indonesian people deaths each year and 25.000 non-smokers deaths. Not only in smokers, a disease caused by exposure to tobacco can also be suffered by farmers. That is because the tobacco farmers have the potential exposure to harmful substances from cigarettes and tobacco itself. Health services located around the site should be able to educate people to behave healthily. In this study, we examined the access of health services toward smoking behavior in smokers who lived in tobacco commodities areas. This study was an analytic research with cross sectional study design. Samples were 100smokers in tobacco commodities areas in Weleri Kendal. Most of respondent are male (96%). They were on their final adult age (29%), worked as farmer (80%), and consumed white cigarette (79%). Most of the respondents went to healthservices when they sick (93%) because the distance to health service was close (69%) and had complete facilities (79%). The bivariate analysis showed there is no association between access to health sevices (p = 1) toward smoking behavior. Improving the provision and improvement of facilities should not be a priority of smoking cessation programs. Next studies is suggested to explore more about the ability of health workers to educate people to stop smoking.Keywords : Health services, facilities, access, smoking, tobacco